P-23 Promoting end of life care choices in an extra care setting – A success story!. (19th November 2022) - Jones, Debbie; Jackson, Kim; Lewis, Mark
Abstract : Despite many residents in extra care settings seeing this as their 'home for life' – there can often be barriers to achieving good end of life care (National End of Life Programme, 2014). Variation in policy, practices, and support systems across extra care organisations may inadvertently affect how death and dying is perceived, potentially giving way to an over-reliance on crisis management approaches. The need for a skilled workforce extends beyond the traditional care teams in hospitals and primary care, and should reflect the ethos that 'all staff are prepared to care' (National Palliative and End of Life Care Partnership, 2021). As a result, the hospice team embarked on a project with Elmridge Court Extra care scheme, to examine the impact of partnership working on their end-of-life practices. Aims: To identify the enablers of good palliative and end of life care in a 41-bedded extra care setting. Methods: Using a tried and tested practice development model (Froggatt, Preston, Eastham, et al., 2018. In : 10th World Congress of the European Association for Palliative Care) combining formal education with on-site role modelling with staff, and dedicated reflective practice sessions (Gravier, Burney & Radermarcher, 2019. InPsych. 41). Results: During 2021, five residents were identified as being in the last 12 months of life. Four died peacefully in their own home with family present, and one was transferred to the hospice. All achieved their preferred place of death. The results reiterate that good end of life care can and does happen in extra care schemes, and staff now recognise that home is a realistic option (NHS England. 2022). Conclusions: Extra care services can provide timely, skilled, individual end of life care with dedicated support, and this model is transferrable across other care settings. The culture of 'sending everyone to hospital' has shifted to a recognition that for some, this is not what they want, and may be futile. Statutory agencies must examine their own commitment to such schemes to enable choice (Local Government Association, 2020), as success is more likely with a whole systems approach.